SPECIFIC PROBLEMS OF THE TERMS "BUSINESS AND ENTREPRENEURSHIP" IN ENGLISH AND UZBEK LANGUAGES - Kamilova Durdona Kozimjonovna (Western European Studies, 2024)
In this article highlights of specific problems of the terms "business and entrepreneurship" in English and Uzbek languages.
Keywords: English and Uzbek languages; terms; research